Il disgusto e la nausea - Vincenzo Cuomo (Kaiak, 2019)
The essay reflects on concepts that have traditionally been understood as a borderline between aesthetics and psychoanalysis: the notion of disgust and that of nausea. Nausea is a psycho-physiological signal that makes us feel our co-existence with a huge number of human and non-human entities. It is for this reason that it should not be confused with the feeling of disgust. The latter, in fact, is a self-defense reaction produced by the significant-machine, while the nausea is a feeling of engulfment, of filling that makes us skid and makes us lose the anthropo-centric orientation. It is an ecological feeling.